Urgensi Sejarah sebagai Ilmu dalam Upaya Penyadaran Kembali Identitas Nasional Bangsa Indonesia di Era Society 5.0 - Adzkiya Zayyan Mauizah; Devi Rizki Apriliani; Sholeh Utomo; Dafis Heriansyah; Naqiyah Naqiyah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to explore the urgency of history as a science in an effort to re-awaken the Indonesian nation identity to the young generation in Era Society 5.0. The method used in this study is use qualitative research method by collecting data from reading written sources such as journals articles, books and other written sources to be analyzed objectively based on the data obtained from these written sources. The results and discussion of this study indicate that the young generation should know the importance of the struggle of the nation's heroes in achieving Indonesian independence and need historical learning as a provision to face the Era of Society 5.0. Through this research, it can be concluded that the provision of history as a science is an alternative step taken in an effort to raise awareness of history as the national identity of the Indonesian nation to the young generation in the Era of Society 5.0. This study recommends historians, educators or history teachers, the government and Indonesian society as a whole in an effort to raise awareness of the importance of studying history, especially Indonesian history which still needs to be explored further in order to reconstruct history properly.